A biomimetic afferent nervous system based on the flexible artificial synapse. (September 2022) - Wang, Kaiyang; Jia, Yunfang; Yan, Xiaobing
Abstract: Biomimetic afferent nervous system (ANS) is urgently needed in the booming development of neuromorphic chips and artificial intelligent robots. It is necessary to make biomimetic ANS stably respond to the real irritation (heat or touch), not the conventionally used electric stimuli, in a manner of low-power-consumption, flexibility and miniaturization. Here, we present a chip-like flexible ANS device by fusing the ion conductive elastomer (ICE) with the MXene artificial synapse. It can not only successfully generate stable response to the joint flexion behaviors and weak pulse at radial artery, but also the plastic neural response can be simulated. Theoretical explanation for the proposed biomimetic ANS device is investigated by integrating the simulated geometry deformation, ion migration theory and trap assisted tunnel effect. Furthermore, the proposed device is applied to mimic an interesting "operant conditioned reflex behavior" by using a typical "trial and error learning" experiment. The transformations from short-term memory to long-term memory during two operant conditioning reflex stages (training and experiencing) are implemented. Conclusively, the sensory behaviors in biological ANS are simulated by the proposed device, which demonstrates its powerful ability of generating plastic neuro-impulse to real stimuli, thereby granting it a new role to realize the anthropomorphic sensation. Graphical Abstract: Herein, a flexible biomimetic afferent nervous system (ANS) is constructed by fusing the biological ion migration in tactile organ with the MXene artificial synapse' working mechanism. It is exploited to mimic the famous operant conditioning flex (OCF) behaviors, for the first time. Moreover, not only the common joint flexion behaviors and weak pulse at radial artery can be detected, but also the plastic neural response can be simulated. ga1 Highlights: Biomimetic afferent neuron system (ANS) is constructed on flexible MXene synapse. Ion migration of tactile organ is replicated by ionic conductive elastomer (ICE). ICE's conductance change is transduced to plastic current by MXene synapse to improve signal-to-noise ratio. The first simulation of operant conditioning flex is accomplished by biomimetic ANS. Energy consumption of one generated neural response is as low as 380 nj.